Level of public knowledge on the use of mefenamic acid painkillers - Muhammad Farid Hasyim; Gerfan Patandung (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Mefenamic acid is a non-steroidal anti-inflammatory drug (NSAID) with analgesic, anti-inflammatory, and antipyretic effects. This medication is used for mild to moderate pain, including headaches, toothaches, postoperative and postpartum pain, dysmenorrhea, and osteoarthritis. This study aims to provide an overview of public knowledge about mefenamic acid pain relievers. Method: This study uses quantitative descriptive research, which conducts direct research on respondents (the community) who are taken as research subjects. This study describes the level of public knowledge about mefenamic acid anti-pain. Results: The most users of mefenamic acid are women, which is 49 people (62.12%), with the most vulnerable age, namely 17-25 years old, as many as 26 people (35.62%), with the most work, which is not working as many as 37 people (50.68%), with the last education of each respondent in high school, which is 35 people (47.95%). Patient knowledge about the use of mefenamic acid reached 75.02%, which was obtained from the processing of data from community research on mefenamic acid, including quite good knowledge. Conclusion: Mefenamic acid is more commonly found in women, especially in young age groups. Most users are unemployed and have a high school-level education background. The level of public knowledge about the use of mefenamic acid is quite good, but further educational efforts are still needed to increase a more comprehensive understanding of the use of the drug. It is recommended that regular counseling be carried out on the appropriate and rational use of drugs, especially for young age groups and people who do not have a background in health education.